Asymmetric Diels–Alder reaction of 3-(acyloxy)acryloyl oxazolidinones: optically active synthesis of a high-affinity ligand for potent HIV-1 protease inhibitors. Issue 71 (17th December 2019) - Ghosh, Arun K.; Grillo, Alessandro; Kovela, Satish; Brindisi, Margherita
Abstract : Asymmetric Diels–Alder reaction of chiral 3-(acyloxy)acryloyl oxazolidinones and synthesis of hexahydro-4 H -3, 5-methanofuro[2, 3- b ]pyranol are described. Abstract : We describe here our investigation of the asymmetric Diels–Alder reaction of chiral 3-(acyloxy)acryloyl oxazolidinones as dienophiles in various Lewis-acid promoted reactions with cyclopentadiene. The resulting highly functionalized cycloadducts are useful intermediates for the synthesis, particularly for the optically active synthesis of 6-5-5 tricyclic hexahydro-4 H -3, 5-methanofuro[2, 3- b ]pyranol (3 ) with five contiguous chiral centers. This stereochemically defined crown-like heterocyclic derivative is an important high affinity ligand for a variety of highly potent HIV-1 protease inhibitors. Among the various dienophiles and Lewis acid-mediated reactions surveyed, 3-(4-methoxybenzoyl)acryloyl oxazolidinone as the dienophile and diethylaluminum chloride as the Lewis-acid provided the desired endo product with excellent diastereoselectivity. The cycloaddition was carried out in multi-gram scale and the cycloadduct was efficiently converted to alcohol 3 with high enantiomeric purity. The optically active ligand was then transformed into potent HIV-1 protease inhibitor 2 .